Awarenesses and practices of people with venous ulcers in treatment with unna boot - Marianne Lopes Robaina; Maria de Lourdes Denardin Budó; Dalva Cezar da Silva; Maria Denise Schimith; Vânia Lúcia Durgante; Bruna Sodré Simon (Universidade Federal de Santa Maria, 2016)
Aim: to describe the knowledge and practices of people with venous ulcers in treatment with Unna boot. Method: qualitative and descriptive research. It was developed in an angiology outpatient clinic of a university hospital inRio GrandedoSul,Brazil. The data collection occurred in October and November 2013 with eight people, through semi-structured interview, injury evaluation forms and medical records. It was used the thematic content analysis in data processing. Results: the knowledges were related to the circulatory cause and practices, with rest and the healing of venous ulcers. The Unna boot was mentioned as beneficial and facilitating treatment, although it can cause some discomfort. Conclusion: the interviewed patients reported to have awareness about the origin of the lesion, performed care practices to improve the venous return and the Unna boot was considered a beneficial treatment